Optical Coherence Tomography and Optical Coherence Tomography Angiography Findings After Optic Neuritis in Multiple Sclerosis - Murphy, Olwen C.; Kalaitzidis, Grigorios; Vasileiou, Eleni; Filippatou, Angeliki G.; Lambe, Jeffrey; Ehrhardt, Henrik; Pellegrini, Nicole; Sotirchos, Elias S.; Luciano, Nicholas J.; Liu, Yihao; Fitzgerald, Kathryn C.; Prince, Jerry L.; et al. (Frontiers in Neurology, 2020)
Background: In people with multiple sclerosis (MS), optic neuritis (ON) results in inner retinal layer thinning and reduced density of the retinal microvasculature. Objective: To compare inter-eye differences (IEDs) in macular optical coherence tomography (OCT) and OCT angiography (OCTA) measures in MS patients with a history of unilateral ON (MS ON) versus MS patients with no history of ON (MS non-ON), and to assess how these measures correlate with visual function outcomes after ON. Methods: In this cross-sectional study, people with MS underwent OCT and OCTA. Superficial vascular plexus (SVP) density of each eye was quantified using a deep neural network. IEDs were calculated with respect to the ON eye in MS ON patients, and with respect to the right eye in MS non-ON patients. Statistical analyses used mixed-effect regression models accounting for intra-subject correlations. Results: We included 43 MS ON patients (with 92 discrete OCT/OCTA visits) and 14 MS non-ON patients (with 24 OCT/OCTA visits). Across the cohorts, mean IED in SVP density was -2.69% (SD 3.23) in MS ON patients, as compared to 0.17% (2.39) in MS non-ON patients (p=0.002). When the MS ON patients were further stratified according to time from ON and compared to MS non-ON patients with multiple cross-sectional analyses, we identified that IED in SVP density was significantly increased in MS ON patients at 1-3 years (p=<0.001) and >3 years post-ON (p<0.001), but not at <3 months (0.21) or 3-12 months post-ON (p=0.07), while IED in ganglion cell + inner plexiform layer (GCIPL) thickness was significantly increased in MS ON patients at all time points post-ON (p≦0.01 for all). IED in SVP density and IED in GCIPL thickness demonstrated significant relationships with IEDs in 100% contrast, 2.5% contrast, and 1.25% contrast letter acuity in MS ON patients (p<0.001 for all). Conclusions: Our findings suggest that increased IED in SVP density can be detected after ON in MS using OCTA, and detectable changes in SVP density after ON may occur after changes in GCIPL thickness. IED in SVP density and IED in GCIPL thickness correlate well with visual function outcomes in MS ON patients.